Patterns of Ecclesiastical Authority: The @Problem of Chicago Succession, 1865-1881 - Gaffey, James P. (Church history, 1973)
The inevitable tension between freedom and order within the Roman Catholic Church has ever been an attractive and rich subject of comment. Perhaps nowhere can this issue be studied with more seriousness and clarity than in the fragile equilibrium between American bishops and priests. The balance within clerical ranks in the United States has long represented a singular combination of authority and obedience which has sought to reconcile itself in a society historically egalitarian and devoid of feudal relationships.